Answer:
f(g(x)) = x
Explanation:
The inverse of a function is a function that "reverses" the other one, meaning that if I input a value x to the first function and get the result y on the second function, I can put the same y value to the second function and it will give me the first x value again.
In this problem we have that:
f(x) is the inverse of g(x) ⇒ f (x) = g⁻¹(x)
g(x) is the inverse of f(x) ⇒ g(x) = f ⁻¹(x)
The problem asks us to find f(g(x))
f(g(x)) = f(f ⁻¹(x)) = x
Therefore, f(g(x)) = x